CDK4 expression in chordoma: A potential therapeutic target. Issue 6 (22nd December 2017) - Liu, Tang; Shen, Jacson K.; Choy, Edwin; Zhang, Yu; Mankin, Henry J.; Hornicek, Francis J.; Duan, Zhenfeng
ABSTRACT: Chordomas are rare bone tumors and treatment is commonly based on a combination of surgery and radiotherapy. There is no standard chemotherapy treatment for chordoma. The aim of this study was to determine the expression of cyclin‐dependent kinase 4 (CDK4) in chordoma and its therapeutic implications. We evaluated CDK4 expression both in chordoma cell lines and in chordoma tissues. Also, we investigated the functional roles of CDK4 in chordoma cell growth and proliferation. Furthermore, the therapeutic implications of targeting CDK4 in chordoma were evaluated. We found CDK4 highly expressed in chordoma cell lines and in a majority (97.7%) of chordoma tissues. Higher CDK4 expression correlated with metastasis and recurrence of chordoma. Treatment of chordoma cells using CDK4 inhibitor palbociclib could efficiently inhibit chordoma cells growth and proliferation. These data demonstrate that targeting CDK4 may be useful as a novel strategy in the treatment of chordoma. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1581–1589, 2018.